2011
DOI: 10.1590/s1516-35982011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Redução da proteína em dietas para tilápias-do-nilo por meio da suplementação de aminoácidos com base no conceito de proteína ideal

Abstract: RESUMO -Este trabalho foi realizado para avaliar os efeitos da redução da proteína da dieta, por meio da suplementação com aminoácidos sintéticos, sobre o desempenho produtivo, a digestibilidade e o diâmetro da fibra muscular de tilápias-do-nilo. Os aminoácidos (lisina, metionina, treonina e arginina) foram suplementados de forma a manter o perfil de aminoácidos da dieta-referência. Foram utilizados 160 peixes com peso vivo médio inicial de 105,7 ± 2,5 g, distribuídos em 16 tanques (1 m 3 cada) e alimentados c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 30 publications
1
5
3
6
Order By: Relevance
“…However, the value observed in the present study was lower than those observed by Furuya et al (2000) and Bomfim et al (2010), who reported 8.7% and 8.9%, respectively. In addition, the specific growth rate of the present study was greater than the values between 3.2% and 5.5% reported by and Righetti et al (2011). These researchers suggest that the use of fish feed formulated with a moderate reduction in the recommended crude protein levels (of 32%) (NRC, 1993;FURUYA et al, 2000;NRC, 2011), that based on the ideal protein concept has also been supplemented with commercial amino acids, does not adversely affect the performance of fish, even at low feeding frequencies (twice daily).…”
Section: Resultscontrasting
confidence: 91%
See 2 more Smart Citations
“…However, the value observed in the present study was lower than those observed by Furuya et al (2000) and Bomfim et al (2010), who reported 8.7% and 8.9%, respectively. In addition, the specific growth rate of the present study was greater than the values between 3.2% and 5.5% reported by and Righetti et al (2011). These researchers suggest that the use of fish feed formulated with a moderate reduction in the recommended crude protein levels (of 32%) (NRC, 1993;FURUYA et al, 2000;NRC, 2011), that based on the ideal protein concept has also been supplemented with commercial amino acids, does not adversely affect the performance of fish, even at low feeding frequencies (twice daily).…”
Section: Resultscontrasting
confidence: 91%
“…In addition, studies have suggested that more precise supplementation with commercially-available limiting amino acids to meet the nutritional requirements of Nile tilapia (FURUYA et al, 2005;BOTARO et al, 2007;BOMFIM et al, 2008;QUADROS et al, 2009;RIGHETTI et al, 2011), tambatinga (ARARIPE et al, 2011), and rainbow trout (YAMAMOTO; SUGITA; FURUITA, 2005) could effectively reduce the use of excessive levels of other amino acids in the feed, thereby reducing levels of nitrogen excreted into the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the diets were provided as five daily meals and successive transfers, it is possible that this procedure matched the differences between the rates of industrial amino acid absorption and those obtained from protein sources (SOUZA et al, 2014). The higher the feeding frequency, the better the match between the concentration of industrial amino acids and those obtained from protein sources, therefore resulting in a higher protein efficiency, which is consistent with the results observed in this study (RIGHETTI et al, 2011;SOUZA et al, 2014;SANTOS et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…A quantidade de proteína da dieta depende de inúmeros fatores inerentes ao peixe, às condições ambientais de criação e à própria dieta. Vários estudos têm buscado o melhor regime de alimentação quanto à qualidade e aos níveis proteicos, com o objetivo de redução dos custos com alimentação, sem causar danos metabólicos aos peixes (Al Hafedh, 1999;Hayashi et al, 2002;Furuya et al, 2005;Botaro et al, 2007;Righetti et al, 2011;Loum et al, 2013).…”
Section: Introductionunclassified